Changing trend of antibiotic susceptibility pattern of Enteric Fever: What is Next? (Journal of Medicine, 2019)
Enteric fever continues to be a major global public health problem, predominantly in the developing countries, including Bangladesh. Mortality rates due to enteric fever can be reduced from 30% to